2014
DOI: 10.1007/s10853-014-8052-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methylimidazole on cellulose/ionic liquid solutions and regenerated material therefrom

Abstract: Cellulose, especially wood-based cellulose, is increasingly important for making everyday materials such as man-made-regenerated textile fibers, produced via dissolution and subsequent precipitation. In this paper, the effect of cosolvents in ionic liquid-facilitated cellulose dissolution is discussed. Both microcrystalline cellulose and dissolving grade hardwood pulp were studied. Three different cosolvents in combination with ionic liquid were evaluated using turbidity measurements and viscosity. The ionic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 41 publications
(47 reference statements)
1
31
0
Order By: Relevance
“…Airgap-and wet spinning of eucalypt dissolving grade pulp in [Emim]OAc and methylimidazole (MIM) was investigated by Olsson et al [208]. Pure [Emim]OAc/cellulose solution was spun at 2.8 m min −1 through 150 µm capillaries.…”
Section: Cellulose Precipitationmentioning
confidence: 99%
“…Airgap-and wet spinning of eucalypt dissolving grade pulp in [Emim]OAc and methylimidazole (MIM) was investigated by Olsson et al [208]. Pure [Emim]OAc/cellulose solution was spun at 2.8 m min −1 through 150 µm capillaries.…”
Section: Cellulose Precipitationmentioning
confidence: 99%
“…As shown in Fig. 2b, the bulk densities of the aerogels were low, ranging from 0?044 to 0?150 g cm 21 .…”
Section: Resultsmentioning
confidence: 89%
“…[1] Most commonly used ILs are imidazolium-based. [34][35][36][37][38][39][40][41][42][43] Röder ). [34,35] Hermanutz et al showed that [BMIM][Cl] can be used for the realization of spinning dopes that contained up to 16.5 wt% cellulose dopes.…”
Section: Cellulose Fiber Spinning Using Il-technologymentioning
confidence: 99%